Intra-articular injection of kartogenin promotes fibrocartilage stem cell chondrogenesis and attenuates temporomandibular joint osteoarthritis progression - Qiu, Jin; Hua, Bingqiang; Ye, Xiaoping; Liu, Xianwen (Frontiers in Pharmacology, 2023)
Kartogenin (KGN) is a small-molecule compound that has been reported to improve the chondrogenic differentiation of mesenchymal stem cells in vitro and to alleviate knee joint osteoarthritis in animal models. However, whether KGN has any effect on temporomandibular joint osteoarthritis (TMJOA) remains unclear. Herein, we first performed partial temporomandibular joint (TMJ) discectomy to induce TMJOA in rats. Histological analysis, tartrate-resistant acid phosphatase staining, and immunohistochemistry showed that intra-articular injection of KGN attenuated cartilage degeneration and subchondral bone resorption in vivo. Further analyses of the underlying mechanisms revealed that KGN enhanced chondrocyte proliferation, increased the number of cells in both superficial and proliferative zones of TMJ condylar cartilage in vivo, enhanced the proliferation and chondrogenic differentiation of fibrocartilage stem cells (FCSCs), and upregulated the expression of chondrogenesis-related factors in vitro. Collectively, in our study, KGN was shown to promote FCSC chondrogenesis and restore TMJ cartilage, suggesting that KGN injections might be a potential treatment for TMJOA.